Answer:
x = 6 , y = -4
Explanation:
Solve the following system:
{-9 y - 3 x = 18 | (equation 1)
3 y + 4 x = 12 | (equation 2)
Swap equation 1 with equation 2:
{4 x + 3 y = 12 | (equation 1)
-(3 x) - 9 y = 18 | (equation 2)
Add 3/4 × (equation 1) to equation 2:
{4 x + 3 y = 12 | (equation 1)
0 x - (27 y)/4 = 27 | (equation 2)
Multiply equation 2 by 4/27:
{4 x + 3 y = 12 | (equation 1)
0 x - y = 4 | (equation 2)
Multiply equation 2 by -1:
{4 x + 3 y = 12 | (equation 1)
0 x+y = -4 | (equation 2)
Subtract 3 × (equation 2) from equation 1:
{4 x+0 y = 24 | (equation 1)
0 x+y = -4 | (equation 2)
Divide equation 1 by 4:
{x+0 y = 6 | (equation 1)
0 x+y = -4 | (equation 2)
Collect results:
Answer: {x = 6 , y = -4